Risk factors of bladder stones in neurogenic lower urinary tract dysfunction: A real‐world study - Möhr, Sandra; Fassbind, Saskia; Gahl, Brigitta; Seifert, Hans‐Helge; Bausch, Kathrin (BJUI compass, 2024)
Objective The objective of this study is to investigate the incidence and risk factors for stone formation and recurrence in patients with neurogenic lower urinary tract dysfunction (NLUTD) in a real‐world cohort. Materials and methods A retrospective cohort study was conducted on all patients with NLUTD who underwent bladder stone treatment between 2010 and 2022. Univariate and multivariate Cox models were used to identify the potential risk factors for stone recurrence. Results Among 114 patients included in the study, 30% experienced stone recurrence. The most common stone components were carbonate apatite phosphate and magnesium ammonium phosphate. The overall recurrence rate was 14 cases per 100 patient years. Neurogenic detrusor overactivity had the highest recurrence rate. Risk factors for stone recurrence in the multivariate analysis were intermittent and suprapubic catheterization, and recurrent urinary tract infection (rUTI). Conclusions Patients experienced multiple bladder stone recurrences. Close monitoring of bladder pressure and UTI with restrictive catheter application may reduce the risk of stone recurrence.